The Syntax of Mainland Scandinavian, by Jan Terje Faarlund (2019) - Peter Svenonius (Maal og Minne)
The Syntax of Mainland Scandinavian (henceforth SMS) is a unique and useful reference work. It has the breadth of coverage of a reference grammar, but unlike most reference grammars of languages with established written traditions, it is not primarily designed for students seeking practical mastery of a language. It presents its subject matter as seen through the eye of a linguist rather than through that of a language teacher or learner (in this respect it resembles certain grammars of less well known languages). On the other hand, it steers clear of linguistic terminology for the most part and does not go into detailed analysis, in contrast to the orange Syntax of series of Cambridge University Press (e.g., Höskuldur Thráinsson 2007 or Haider 2010), to take a point of comparison.